CENTRAL WORDS OF THE DEAN FOR THE 38 ANNIVERSARY OF THE FACULTY OF LEGAL AND POLITICAL SCIENCES OF THE UNA-PUNO - Boris Gilmar Espezúa Salmón (2020)
Dr. Peter Manzaneda, Department Director. Dr. Carlos Ramírez. Principal. Dr. Juan Casazola Director of the Postgraduate Law Unit. Dra. Diana Dueñas, Director of the Research Office. Dear fellow teachers, fellow administrators, esteemed students of our Faculty of Legal and Political Sciences. On August 8 of every year we celebrate our anniversary for 38 years. And it is a reason to remember a splendid career that we have had, but also to envision the future that we have to navigate. And it is from this perspective that we have to know how to guide our actions so that we maintain, on the one hand, the pedestal of prestige and social recognition that we have obtained with effort and dedication, but also on the other hand, to emerge better horizons in order to become the best Faculty of Right of the south of Peru, because the academic conditions, like the human ones, will allow us to reach better and higher peaks of progress and consolidation, with which it is not an absurdity to yearn for this goal.